URGENSI WEB DALAM MENDUKUNG PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Muammar Qadafi (STAI Asy-Syukriyyah, 2023)
The web is an application that contains multimedia documents, such as animation, text and video. This media is expected to support the PAI learning process. The purpose of web optimization research in PAI learning. This type of research uses field research with qualitative methods, where researchers come directly to the object of research to make observations, then confirmed through interviews with PAI teachers and class XI AKL students. The results of this study: the web for educators can easily motivate learning by animating teaching materials, attracting students' attention so as not to get bored quickly, delivering material through audio visual and making students easily master the material through the web. second, learners; The web as a tool to find references, learn to create animated material using Canva and master the material through practice.